Digital Competencies and Experience In Partnership Program on SMEs Performance - Muhammad Reza Aulia (Journal Research of Social Science, Economics, and Management, 2023)
Small medium enterprises need to improve their digital competencies but the lack of awareness of digital services and outcomes is a concern in business environments is one of the business units that help the country a lot in reducing the unemployment rate. The main objective of this study is to determine the direct and indirect effects of experience, digital competencies, partnership program on the SMEs performance. The approach in this research is causal research (cause and effect). The population in this study is the SME business actor who are fostered. While the sampling technique used a purposive sampling where sample used in this study is 241 SMEs business actors who are participating in the partnership program. Data collection techniques used a questionnaire with an ordinal measurement scale. Data analysis used Smart PLS 4 based Partial Least Square. Based on the results of the direct effect analysis, it shows that Digital Competence has a significant effect on the Partnership Program and SMEs Performance; Experience has a significant effect on Digital Competence, Partnership Programs, and SMEs Performance; and the Partnership Program has a significant effect on SMEs Performance. Meanwhile, the results of the indirect effect analysis show that Digital Competence has no significant effect on performance (only direct influence); Experience has a significant influence on the Partnership Program and SMEs Performance.